Digitalisasi sebagai strategi peningkatan kualitas pelayanan Bank Syariah Indonesia (BSI): Studi literatur - Anggrainie, Agustina (Maliki Interdisciplinary Journal, 2024)
Bank Syariah Indonesia (BSI) as one of the main players in the sharia banking industry in Indonesia is responding to this development by gradually adopting digitalization. Digitalization is not just an innovative step, but an urgent strategic need. This is necessary to maintain competitiveness amidst increasingly fierce global competition, as well as meeting customers’ increasingly high expectations for fast, safe and easily accessible services. Digital transformation is expected to minimize obstacles that have been an obstacle for customers, such as inconsistencies in service quality between branches which often cause long queues, slow processes, and difficulty in accessing various sharia products that customers want. Through digitalization, BSI strives to create more uniform and easily accessible services throughout its branch network. So this research aims to dig deeper into sharia banking strategies in improving service quality using the literature study method of previous researchers which is in accordance with the topic of discussion in this research. The research results show that Islamic banks’ strategy is to improve service quality through banking digitalization by presenting e-banking features which consist of 5 main services, namely ATM, SMS banking, mobile banking, telephone banking and internet banking. Then Bank Syariah Indonesia (BSI) accelerated digital banking services through BSI Mobile.